Motivational conditions experienced by diverse adult learners in cohort-based accelerated degree programs: quantifying learner perceptions for assessment and enhancement of adult motivation to learn - Barnes, Pamela Kay (Kansas State University, 2012)
This study measured levels of conditions eliciting intrinsic motivation to learn and examined the correlation of those measures with learner-perceived level of learning. Acquired from adult learners participating in one Midwestern University’s cohort-based degree programs, data helped determine the extent to which learners perceived the presence of four conditions—inclusion, attitude, meaning, and competence—in both classroom and out-of-classroom learning environments. Additionally, the data helped determine which environment and specific conditions most closely correlated with learner-perceived level of current learning; and provided insight into experiences adult learners found positively or negatively impacting motivation to learn. Surveys were administered in-person to 137 of 150 students within 13 randomly selected cohorts. The survey instrument included a single overall learning attitudinal statement, two Likert scales (classroom and out-of-classroom) each comprised of subscales (inclusion, attitude, meaning, and competence) operationalizing the Motivational Framework for Culturally Responsive Teaching (Framework), a brief demographic section, and a concluding open-ended question regarding experiences impacting motivation to learn. The study used non-parametric analysis to examine dependent variables, motivation conditions, with respect to independent variables; age, gender, race, and degree-level. Additionally, non-parametric analysis examined correlation between condition measures and learner-perceived overall learning. Significant differences were found in two demographic categories. Underrepresented race/ethnicity students (as a combined category) rated overall out-of-classroom conditions higher than predominant race/ethnicity students; and, associate-level students rated classroom conditions lower than bachelors and masters-level students. Significant differences also occurred in subscales. Female students rated classroom attitude conditions higher than males; underrepresented students rated classroom attitude and competence, and out-of-classroom attitude, meaning, and competence, higher than predominant students; associates-level students rated classroom inclusion lower than both bachelors and masters-level students; and both associates and masters-level students rated classroom competence lower than bachelors-level students. All conditions, in both environments (classroom and out-of-classroom), were significantly correlated with learner-perceived level of learning; and the classroom scale demonstrated considerably stronger correlation than did the out-of-classroom scale. Of all subscales, both classroom and out-of-classroom meaning demonstrated the strongest correlation with learner-perceived level of learning. Forty-eight respondents (35% of sample) offered responses to the survey’s concluding statement. Of those respondents offering comments in regard to classroom motivation, instructor characteristics were most often noted. And, of those commenting on out-of-classroom motivation, team formulation and characteristics were predominant. Through the creation of the Motivation Conditions in Learning Instrument™, this study produced benchmark measures for each Framework condition experienced in both cohort-based classrooms and out-of-classroom team learning; identified differences in measures across demographic categories; and identified correlation of measures with learner-perceived level of learning. Finally, the study provided insight into learner experiences impacting motivation to learn.
Keywords: Adult Education; Motivation to learn; Accelerated degree programs; Cohort-based learning; Adult Education (0516)